Factors associated with completion of intensive adherence counseling among people living with HIV at a large referral hospital in Uganda: a retrospective analysis - Solomom Paul Okot; Jonathan Izudi; Ronald Ssenyonga; Juliet Ndimwibo Babirye (BMC, 2024)
Abstract Background Among people living with HIV(PHIV) with unsuppressed viral load after six or more months of anti-retroviral therapy (ART), three intensive adherence counseling sessions (IAC) sessions are recommended. However, there is limited information about IAC completion rates. We investigated the factors associated with IAC completion among PLHIV with an unsuppressed viral load on first and second-line ART in mid-western Uganda. Methods In this retrospective review of medical records, we abstracted routine HIV data between January 2018 and September 2019 at the Fort Portal Regional Hospital. IAC completion was the primary outcome measured as the receipt of ≥ 3 consecutive good ART adherence scores of ≥ 95.0% during the IAC sessions, spaced one month apart within three months. The modified Poisson regression analysis with robust standard errors was used to determine factors associated with the outcome, reported as risk ratio (RR) and 95% confidence interval (CI). Results We studied 420 participants of whom 204 (48.6%) were aged 20-39 years (mean age, 33.6 ± 13.3 years) and 243 (57.9%) were female. 282 (67.1%) participants completed their IAC sessions. Secondary or higher levels of education (Adjusted RR (aRR) 0.79, 95% CI 0.64-0.98), no follow-up for IAC (aRR 0.76, 95% CI 0.67-0.87), malnutrition (aRR 0.65, 95% CI 0.43-0.99) were associated with a lower likelihood of IAC completion while being in a separated/widowed or divorced relationship (aRR 1.23, 95% CI 1.01-1.49) was associated with a higher likelihood of IAC completion. Conclusions We found a low IAC completion rate compared to the desired target of 100%. Nutritional support for malnourished PLHIV receiving IAC, follow-ups, and targeted health education on the importance of IAC are needed to improve the IAC completion rate.